Levantamento fitossociológico e interferência de plantas daninhas na cultura do feijão-caupi na savana de Roraima - Silva, Denysson Amorim da (2015)
The cowpea cultivation has great importance for the northern region, particularly for the poorest population. One of the major problems encountered in this culture is the competition with weeds. Determining the critical period of weed interference in local conditions is of paramount importance so that control strategies can be planned to maximize the profitability of production. After a certain period of the cycle in which the crop must be kept free of interference, it is also necessary to evaluate and identify weeds that most influence on competition. The objective of this study was to evaluate the phytosociology, characterization and interference of weeds in cowpea cultivation in Roraima savannah. The experiment was conducted at the Federal University of Roraima Campus Cauamé in the agricultural year 2013, under irrigated conditions using to grow cowpea BRS Guariba in no-till system for evaluation in dry and green beans grain. For phytosociologic evaluation, the following variables were taken: frequency, density, bundance, relative frequency, relative density, relative abundance and importance of species of value index, and further descriptions of botanical classes, families, species, type of propagation cycle life and growth habit. For sampling, was used iron square, 0.50 x 0.50 m, randomly released twenty-five times in the experimental area of 1.508 m2. The weeds were identified and quantified by the sum of the samples obtained by the launch of the square. For the production of components were evaluated: pod length (CMV), number of seeds per pod (NGV); and a sample of 05 plants in the useful area: Plant atura (ALT); and in all plants of the useful area of the plot: the number of plants (NPL); weight of 100 grains in grams (M100G), number of pods per plant (NVP) and production of dry beans - PROD (productivity - kg ha-1). To assess the critical period of competition culture has been fully maintained in clean (control) and dirty (coexistence) over the cycle by periods: 0-10, 0-20, 0-30, 0-40, 0-50 and 0-60 (harvest). Based on the regression equation obtained for grain yield was determined periods of weed interference PAI (the period before interference), TPIC (total period to prevent interference) and PCPI (critical period of interference) using as parameter tolerance level of 5% reduction in the productivity of cowpea, in relation to the experiment treatments. In the experimental area were identified 38 species belonging to seven families from mostly (68.4%) botany class of Dicotyledons. Among the species collected in the area, the botanical family Fabaceae (28.9%), Poaceae (26.3%), Asteraceae and Malvaceae (15.8%). The species with the highest importance value index were: Digitaria horizontalis with 44.66% preceded by Cyperus flavus with 34.13%, with 22.87% island Digitaria, Cyperus sp, with 16.18% and Brachiaria plantaginea with IVR 14.75%, which have importance in the same order of magnitude and must be included in management strategy. The area showed great spatial heterogeneity of weeds, represented by several species, mostly herbaceous perennials the type and spread exclusively sexual. The critical period for weed control for dry grain production must consider what goes from the 3rd day after crop emergence up to 54 days. And for the green bean that goes from the 3rd day after crop emergence up to 49 days. The maximum yield was obtained when kept free culture weed throughout cycle, about 1026 kg ha-1 for dry grain and 1879 kg ha-1 for green beans, and lower when it maintained the culture in competition throughout cycle with 383 kg ha-1 and 259 kg ha-1, respectively, reducing crop yield by about 63% for dry grain and up to 86% for green beans.